Gender Inequality, Health Rights, and HIV/AIDS among Women Prisoners in Zimbabwe - Nirmala Pillay; Dzimbabwe Chimbga; Marie Claire Van Hout (Harvard FXB Center for Health and Human Rights, 2020)
Zimbabwe has successfully reduced its HIV prevalence rate and AIDS-related deaths in recent years, but women, particularly those who are in prison, remain at high risk. Poor prison conditions, discrimination, stigma, and the neglect of the sexual and reproductive health of women prisoners living with HIV result in poor health outcomes for women prisoners. Inadequate and inappropriate health provision in prison is a breach of their human rights and a public health problem. This paper analyzes the political commitment of Zimbabwe to address the underlying determinants of health by incorporating into its health laws and policies measures that promote the health rights of women prisoners living with HIV.